Comparison of linear functions to estimate growth performance and feed intake variations pattern in growing and finishing pigs in high ambient temperature - Lee, N.; Choi, J. W.; Ko, H. S.; Ohh, S. J.; Kim, Y. H.; Jang, A. R.; Kim, J. S. (Diponegoro University, 2019)
High ambient temperature (AT) is a major constraint on efficiency of farming in pig production. Results of reported studies assessing the influences of high AT on pig performance are highly variable, particularly in pigs with different body weight (BW). Therefore, a meta-analysis from ISI Web of Science and PubMed was operated to explain variations of average daily feed intake (ADFI) and average daily gain (ADG) in the reports across literatures during high AT in growing or finishing pigs. Pigs were divided to three BW categories as LOW (46 to 65 kg), MED (65< to 85 kg), and HGH (85< kg). The significant effect of AT on ADG were observed in LOW, MED, and HGH categories. The analysis of variance (ANOVA) for multiple linear regression shows significance of linear relationships between both ADG and ADFI, and AT and BW as: ADGLOW= 1260-19.9*AT+2.09*BW, ADGMED= 1546-22.5*AT-0.88*W, ADGHGH= 1893-31.9*AT-2.40*BW, ADFILOW= 1756-35.0*AT+24.6*BW, ADFIMED= 2793-49.6*AT+12.5*BW, and ADFIHGH= 4172-59.0*AT+0.74*BW. The significant effect of temperature on gain to feed ratio (G:F) was observed in LOW and HGH categories. The ANOVA for multiple regression revealed evidence on high significance of linear relationships between G:F and AT: G:FLOW =0.80+0.02*AT+0.02*BW, G:FMED= 0.95+0.02*AT+0.02*BW, and G:FHGH= 0.78+0.05*AT+0.01*BW. The overall results of mixed model analysis show that the significant interaction between BW and AT means that pigs in heavier category have lower G:F when temperature increases. In conclusion, high AT linearly decrease the ADG, ADFI, and G:F of growing and finishing pigs.